Persepsi Mahasiswa terhadap Tingkat Otomatisasi Berbasis AI pada Keamanan Data dalam Birokrasi - Aruming Sekar Mawarni; Destian Imam Zaky; Rizka Dinda Widiyanti; Amanda Rizka Amelia; Anggraeni Hendra Divani (Institut Nalanda, 2026)
The development of information technology drives digital transformation in government systems, including the application of Artificial Intelligence (AI) in managing bureaucratic data security. The utilization of technology is expected to improve work efficiency, transparency, as well as the quality of public services, but it also raises various perceptions regarding the benefits and risks of its use. This study aims to analyze students' perceptions of the level of AI-based automation in maintaining data security in bureaucratic systems. The study uses a quantitative approach with a survey method through the distribution of questionnaires to students selected using random sampling techniques. The data obtained were analyzed using descriptive statistics to describe respondents' perception trends regarding the implementation of AI. The results of the study show that the majority of students have a positive perception of the use of AI in bureaucracy. AI is considered capable of enhancing data security, accelerating threat detection, reducing human errors, and supporting transparency in information management. In addition, respondents believe that future bureaucracy will increasingly rely on AI technology. Nevertheless, students still show a critical attitude concerning potential risks, such as data leaks, information misuse, and the need for clearer regulations. The findings indicate that the acceptance of AI technology in the bureaucratic sector is quite high; however, its implementation requires strengthening regulations, improving digital literacy, and continuous system monitoring so that the use of AI can be carried out effectively, safely, and sustainably in supporting digital transformation.